Humanoid robot push recovery through walking phase modification - Adiwahono, Albertus Hendrawan; Chee-Meng Chew; Weiwei Huang; Van Huan Dau (2010 IEEE Conference on Robotics, Automation and Mechatronics, 2010)
Push recovery is an important capability that needs to be included while developing a robust humanoid robot walking scheme. In this paper we propose an overall control system and a push recovery controller for humanoid robot walking. When the robot is pushed, the algorithm will modify the walking phase to maintain walking, while considering the practical constraints. 3D simulation results of the walking phase modification approach are presented and its effectiveness for push recovery during walking is discussed.